2019
DOI: 10.1108/ijhcqa-02-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Customized patient clothing and patient satisfaction

Abstract: Purpose To respect the patients’ physical privacy, they should be provided with proper clothing that prevents the exposure of unnecessary parts of the body. The purpose of this paper is to evaluate patient satisfaction upon wearing customized, high-coverage, procedure-specific dresses. Design/methodology/approach New designs of clothing adapted for different kinds of procedures, and offering a good coverage of the body and easy access to the required parts were compared with regular patient clothing. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
7
0
8
Order By: Relevance
“…Hospital patient attire perpetuates the “sick role” and further widens the gap between provider and patient (4,5). The ultimate goal of introducing PALS is to return dignity, control, and comfort to people, which is frequently stripped (literally) upon hospitalization (2,17). Enhancing patient privacy, dignity, and comfort returns some control to patients and may allow them to cope better with their respective disease processes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Hospital patient attire perpetuates the “sick role” and further widens the gap between provider and patient (4,5). The ultimate goal of introducing PALS is to return dignity, control, and comfort to people, which is frequently stripped (literally) upon hospitalization (2,17). Enhancing patient privacy, dignity, and comfort returns some control to patients and may allow them to cope better with their respective disease processes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Patients experience reduced opportunities for self-expression and feel depersonalized when wearing uniformly-shaped patient clothing [ 14 ]. Khorshid et al [ 6 ] reported that when patients suffered stress and physical constraints during hospitalization and the recovery phase, positive emotions about clothing were effective in improving their healing and self-esteem. Therefore, when considered in terms of the treatment process, patient clothing is required not only to have a physical function for convenience of treatment, but also to influence the patient’s emotions by the quality of its design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, patient clothes are often designed for medical treatment purposes and are in the form of pajamas or a gown for ease of treatment, which can cause anxiety about exposure if worn without underwear. For the safety of patients, patient clothing design must proper ease of access to enable comfortable treatment, but must also create a psychological environment that allows the patient to feel cared for and provides emotional comfort [ 6 ]. Color is an important design element and has a strong relationship with emotions [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the hospital provided garment, the Johnny, can provide some coverage, its design is far from the comforts of the clothing children are used to wearing outside of the hospital. The patients' and parents' positive feelings about their clothes can help improve their feelings of wellness and self‐respect while recovering (Vaskoo‐Eshkevari et al, 2019). Despite this, it appears that clothing is an overlooked aspect of hospital care (Edvardsson, 2009).…”
Section: Introductionmentioning
confidence: 99%